Investigating nuclear structure near N=32 and N=34: precision mass measurements of neutron-rich Ca, Ti, and V isotopes - Porter, William Stevens; Dunling, E.; Leistenschneider, E.; Bergmann, J.; Bollen, G.; Dickel, T.; Dietrich, Kilian; Hamaker, A.; Hockenbery, Z.; Izzo, C.; Jacobs, A.; Javaji, A.; et al. (Physical review, 2022)
Nuclear mass measurements of isotopes are key to improving our understanding of nuclear structure across the chart of nuclides, in particular, for the determination of the appearance or disappearance of nuclear shell closures. We present high-precision mass measurements of neutron-rich Ca, Ti, and V isotopes performed at TRIUMF's Ion Trap for Atomic and Nuclear science (TITAN) and the Low Energy Beam and Ion Trap (LEBIT) facilities. These measurements were made using the TITAN multiple-reflection time-of-flight mass spectrometer (MR-ToF-MS) and the LEBIT 9.4T Penning trap mass spectrometer. In total, 13 masses were measured, 8 of which represent increases in precision over previous measurements. These measurements refine trends in the mass surface around N=32 and N=34, and support the disappearance of the N=32 shell closure with increasing proton number. Additionally, our data do not support the presence of a shell closure at N=34.